The Network Mechanism of the Central Circadian Pacemaker of the SCN: Do AVP Neurons Play a More Critical Role Than Expected? - Mieda, Michihiro (Frontiers in Neuroscience, 2019)
The suprachiasmatic nucleus (SCN) functions as the central circadian pacemaker in mammals and entrains to the environmental light/dark cycle. It is composed of multiple types of GABAergic neurons, and interneuronal communications among these neurons are essential for the circadian pacemaking of the SCN. However, the mechanisms underlying the SCN neuronal network remain unknown. This review will provide a brief overview of the current knowledge concerning the differential roles of multiple neuropeptides and neuropeptide-expressing neurons in the SCN, especially focusing on the emerging roles of arginine vasopressin-producing neurons uncovered by recent studies utilizing neuron type-specific genetic manipulations in mice.